5x+3(-x+11)=3

Simple and best practice solution for 5x+3(-x+11)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+3(-x+11)=3 equation:



5x+3(-x+11)=3
We move all terms to the left:
5x+3(-x+11)-(3)=0
We add all the numbers together, and all the variables
5x+3(-1x+11)-3=0
We multiply parentheses
5x-3x+33-3=0
We add all the numbers together, and all the variables
2x+30=0
We move all terms containing x to the left, all other terms to the right
2x=-30
x=-30/2
x=-15

See similar equations:

| 0=-(x-7)^2+3(x+2)-3x | | 5.5y+3.5=5y-5 | | 4x4-7x2=0 | | 1/2=b/8 | | 13+4y=81 | | 2u2+2u2= | | p+6=52 | | X+0.25x=79.00 | | 2r²-5r-12=0 | | x²=1/100 | | 7÷2x=4+1÷2x | | 1+x-1+12x=12x-3 | | 3(y-1)=2(2y-6)* | | -8x-2x=7-11x | | 3(2x-1)+5=14* | | 5x-8=x+4* | | 5+x+11x=11x+11 | | 1+3b-b=-11 | | 2m/6-1=-9 | | 2-11m=3-10m-6 | | 282=3x+6(7x+2) | | -9-2m=18-5m | | -186=-98x+43 | | 18x−58=84 | | 0=y^2-15y+64 | | 18x−58​ =84 | | 19/24=12/x | | 8m+6/2+6=10m+5/7 | | 5(x+1)+6(x-2)=7(x+3) | | 4(5x-8)=-92 | | p+5=8.7 | | 3x^+31=79 |

Equations solver categories